"Only Connect!" Social Capital, Resilience, and Recovery. Issue 1 (24th April 2013) - Tierney, Kathleen
Abstract Daniel Aldrich's Building Resilience combines theoretical insights on the role of social capital in community life and extensive empirical research on its impact on recovery following four disasters. In her review of this major contribution, Kathleen Tierney discusses the conceptualization and measurement of disaster recovery and resilience and the relevance of social capital in its multiple forms. She then highlights potential contributions of supra‐local entities to improving disaster outcomes that Aldrich seems reluctant to consider.